KURIKULUM 2013 PERSPEKTIF FILSAFAT PENDIDIKAN ISLAM: Tela'ah Pemikiran Filosofis Kurikulum 2013 - Lalu Muhammad Nurul Wathoni; Armizi Armizi (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2018)
The philosophical cornerstone of Curriculum 2013 states that there is no educational philosophy that can be used specifically for the development of the curriculum 2013. This curriculum becomes like a 'gado-gado' which must be processed in such a way as to be implemented, consequently there are multiple interpretations among stakeholders in the education unit As happened in some schools. Whereas with a clear philosophical foundation, the direction and objectives of the curriculum become clear. Moreover, many people do not really understand about the philosophical foundation in the curriculum. So, this is the background why researchers interested in researching the 2013 curriculum from the perspective of Islamic education philosophy. The findings in this articel are that 1) the development of the curriculum in 2013 is to improve the basis of change in the attitude, knowledge and skills of the students in order to create a good character education (akhlâkiyyah-insâniyyah), and minimize poverty, ignorance and backwardness of civilization of the nation. 2) The 2013 curriculum has the foundation of philosophy of al-hadhari philosophy, which is principled on civilization, culture and progress by looking at important moral values ​​(morals), knowledge and skills (competence). The philosophical thoughts of Islam that color the Curriculum 2013 are Al-Dîniy al-Muhâfizh, Al-Dîniy al-‘Aqlâniy, Al-dzarâi’iy dan Rekonstruksionisme. and reconstructionism. 3) the view of Islamic education philosophy towards the development of the Curriculum component of 2013 that is a. SKL is strongly influenced by Bloom's taxonomy (cognitive, affective and psychomotor) but must be developed with a spiritual-transcendental domain, ie faith; b. The thematic-itegrative content standard can be developed based on teo-anthropcentric theory; c. The scientific approach of the scientific appoach approach to the learning environment is developed from the tri-center of education to the educational center-chess, ie family, community, mosque and school; and D. Assessment that is bebasis process (authentic) should not be limited attitude assessment on two subjects only (PAI and PPKn). And 4) the implications of Curriculum 2013 on the development of Islamic education curriculum in Indonesia is an integrated, inter-active, interactive, active, collaborative, and multidiscipline transfomative learning of Islam; development of Islamic science; and holistic education on Islamic education.